Zur Rezeption der Dramen von Friedrich Schiller auf der polnischen Bühne im Großherzogtum Posen (1815-1871) und in der Provinz Posen (1871-1918) - Czekańska, Małgorzata (Studia Germanica Posnaniensia, 2018)
During the Prussian times in Poznan, F. Schiller's dramas were performed both in the German Stadttheater and the Polish Theatre. They were popular among Poles because of three reasons: 1) The audience mostly consisted of the graduates of German schools, so there were no language problems; 2) performer's benefits were extremely attractive with most popular actors, who often chose F. Schiller's tragedies to show their acting abilities; 3) the independent ideas of Schiller's tragedies compensated for the lack of forbidden Polish literature.